2023
DOI: 10.3389/fcell.2022.1043259
|View full text |Cite
|
Sign up to set email alerts
|

miR-23a/b clusters are not essential for the pathogenesis of osteoarthritis in mouse aging and post-traumatic models

Abstract: Osteoarthritis (OA), the most prevalent aging-related joint disease, is characterized by insufficient extracellular matrix synthesis and articular cartilage degradation and is caused by various risk factors including aging and traumatic injury. Most microRNAs (miRNAs) have been associated with pathogenesis of osteoarthritis (OA) using in vitro models. However, the role of many miRNAs in skeletal development and OA pathogenesis is uncharacterized in vivo using genetically modified mice. Here, we focused on miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Previous studies showed that the miR-23-27-24 cluster is expressed in the lung, skeletal muscle, and liver [ 18 ]. Our recent previous study demonstrated that the miR-23-27-24 cluster is expressed in these organs as well as in the CNS [ 28 ]. Since the miR-23-27-24 cluster is expressed in skeletal muscles, it could be argued that motor impairment upon miR-23-27-24 cluster deletion is possibly due to the loss of skeletal muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the miR-23-27-24 cluster is expressed in the lung, skeletal muscle, and liver [ 18 ]. Our recent previous study demonstrated that the miR-23-27-24 cluster is expressed in these organs as well as in the CNS [ 28 ]. Since the miR-23-27-24 cluster is expressed in skeletal muscles, it could be argued that motor impairment upon miR-23-27-24 cluster deletion is possibly due to the loss of skeletal muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the expression of miR-23a/b clusters in the liver, lungs, skeletal muscles, and CNS [14,18,19]. In this context, the present study assessed changes in the expression of these clusters in the organs of myelin-specific miR-23a/b cluster-deficient mice.…”
Section: Discussionmentioning
confidence: 92%
“…Genotyping was performed using genomic deoxyribonucleic acid extracted from the tail tip, as previously described [18,19]. The KO mice were specifically identified using PCR with the primers 5 ′ -GCA TTA CCG GTC GAT GCA ACG AGT GTA GAG-3 ′ and 5 ′ -GAG TGA ACG AAC CTG GTC GAA ATC AGT GCG-3 ′ .…”
Section: Animals and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation